Belarus : Recent Economic Developments. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1996)
This paper reviews economic developments in the Republic of Belarus during 1994-96. After several years of efforts at structural reform and stabilization during which little progress was made, following presidential elections in mid-1994, the authorities adopted a wide-ranging adjustment program aimed at reducing inflation, increasing the market orientation of the economy, and creating the conditions for a resumption of economic growth. The reform program was reinforced in the first half of 1995, and key macroeconomic data for 1995 show that the program has had some success.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet